Tratamiento biológico de la difteria - Dasso, Héctor (1937)
1st That the toxin and the germ are the same thing, under the Biological point of view of immunity. 2rd That diptheria can be cured with the toxin, as with the germs which produce it. 3rd That a state of immunity for diphtheria can be provoked, with the one element, as well as, with the other. 4th That serotherapy is simply a vehiculization (act as vehicle) of the formed antibodies, which favour the disintegration of the albumins of the germs, and the toxins, by the iunoculated body. 5th That the germs, as well as, the toxin are capable of producing two fundamental substances, which are diametrically opposite, in their biological role, one variety of them are the Lisinas, which structurally and functionally alter the cells of the tissues (Disease), and the others are the Haptinas, which promote the cure of the disease. 6th Deducting from this conception, that the toxin, as well as the germ, depriving them of their albuminons part which is capable of producing Lisinas, can be utilized as active Bacterial remedies against diphtheria.